Salinity tolerance of Round Goby: Informing invasion potential in North American coastal watersheds - Kelsey Alvarez del Castillo; Suresh A. Sethi; Eugene Won; John Maniscalco; Richard Pendleton; Eliza Ryan; Lars G. Rudstam (PLoS ONE, 2025)
Since being introduced into the Laurentian Great Lakes in the 1990s, round goby (Neogobius melanostomus) has spread rapidly, reaching the Hudson River Estuary, NY in 2021. To address the expansion potential into saline environments from this North American coastal invasion front, we experimentally assessed the salinity tolerance of adult round gobies. Water temperatures vary widely in temperate aquatic ecosystems, and our study is the first to investigate the effect of temperature on the salinity tolerance of round goby, conducting tolerance trials at three temperatures: a preferred temperature of 20°C, 26°C reflective of summer conditions, and 5°C reflective of winter conditions. Adult round gobies were subjected to weekly salinity increases of 3 parts per thousand (ppt), concluding at 33ppt. Study specimens were monitored for stress cues (behavior changes and color changes), and mortality. We found significant salinity tolerance differences dependent on water temperature, with the highest tolerance at 5°C and the lowest tolerance at 26°C. By 30ppt, survival was 87% at 5°C and only 7% at 26°C. Based on mortality results, round goby expansion may occur year-round into brackish portions (<21ppt) of the Hudson River Estuary as far south as the Harlem River. This would open access to portions of Long Island Sound, potentially rendering other coastal watersheds to be at risk of invasion. However, temperature-dependent salinity tolerance findings suggest round goby expansion potential into high salinity habitats may be seasonally dependent, with expansion opportunities occurring in colder months and expansion barriers occurring in warmer months. To assess longer term survival and body condition, another experiment maintained round gobies at four sustained salinities (≤ 21ppt) for ten weeks at 20°C. Growth and hepatosomatic index at 21ppt were significantly lower (p<0.001) than at 1, 9, and 15ppt, indicating sustained exposure to higher salinities may affect energy stores, potentially limiting establishment potential.